Three Leg Inverter Control based on Laguerre Model Predictive Controller - Rehiara, Adelhard Beni; Rumengan, Yanty; Sarungallo, Pandung; Hendri, . (Engineering, Technology & Applied Science Research, 2024)
An inverter is a power electronic device that converts Direct Current (DC) to Alternating Current (AC). A three-leg inverter was used to convert DC to AC in a three-phase form. The increasing need to integrate renewable energy into the power grid has increased the demand for this type of converter. In this paper, a Laguerre-based Model Predictive Controller (LMPC) is proposed to control a three-leg inverter under load variation. The proposed LMPC algorithm was designed to optimize the inverter performance and was compared with traditional Sinusoidal Pulse Width Modulation (SPWM) methods. Simulations were conducted under various load conditions including resistive (R), capacitive (RC), and induction motor loads. The results demonstrate that the LMPC controller outperforms the SPWM methods, providing better performance and lower Total Harmonic Distortion (THD) values. The THDs of the voltage and current achieved by the LMPC controller were below 1.5%, complying with IEEE 519-2014 standards. However, the current THD increased to 7.18% under the induction motor load.